1985
DOI: 10.1021/jf00061a040
|View full text |Cite
|
Sign up to set email alerts
|

Glucan biosynthesis in red beet root microsomes and tissue slices

Abstract: As the first step in determining whether polysaccharide biosynthetic enzymes can be utilized to improve textural properties in cut vegetables, the glucan synthase II of red beet root microsomes and tissue slices was characterized. In microsomes, maximal rates of glucose incorporation using uridine diphosphate glucose (UDPG) were obtained at pH 7.0 with cellobiose and 5 mM Mg2+. Approximately 30% of the substrate was incorporated into products. Products were partially solubilized by treatment with /3(l-*-3)and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…2, middle). These results are consistent with previous work, in which PM vesicles partitioned at 38% to 40% Suc, whereas tonoplast vesicles are found at 25% to 28% Suc (Poole et al, 1984;Wasserman et al, 1985).…”
Section: Membrane Distribution Of Pmip31 and Pmip27supporting
confidence: 93%
“…2, middle). These results are consistent with previous work, in which PM vesicles partitioned at 38% to 40% Suc, whereas tonoplast vesicles are found at 25% to 28% Suc (Poole et al, 1984;Wasserman et al, 1985).…”
Section: Membrane Distribution Of Pmip31 and Pmip27supporting
confidence: 93%
“…Microsomal and plasma membrane preparations contain high levels of activity (27) and the enzyme is relatively stable (9). Like other -(41,3)-E-glucan synthases it is readily solubilized by digitonin (9,10).…”
mentioning
confidence: 99%
“…It is currently not known whether the enzyme activity we are measuring is the one found in terminal complexes. In a previous study, it was shown that the reaction product of the microsomal system was mixed ,3-1,3 and ,8-1,4 glucan and not true cellulose (25). The question of whether glucan synthase activity measured in vitro is catalyzed by the same complex that synthesizes cellulose in vivo has been the subject of much speculation.…”
Section: Resultsmentioning
confidence: 99%